Translating copulas and pseudo-copulas from Italian to Spanish - Edo, Miquel (Círculo de Lingüística Aplicada a la Comunicación, 2014)
Translating copulas and pseudo-copulas from Italian to Spanish. The lack of symmetry in the use, and in particular the deletion, of copulas between Italian and Spanish requires translators to adopt strategies to avoid over-use or cacophonies of these common verbs. Similarly, if we analyse pseudo-copulas in both languages we can see that there are slight differences in the desemanticization and frequency of use of each pseudo-copula. For this reason it is important to propose guidelines which, case by case, provide translators with the necessary skills to switch one pseudo-copula for another, substitute pseudo-copulas for copulas, or vice versa.
Keywords: copulas; modal pseudo-copulas; aspectual pseudo-copulas; contrastive linguistics Italian-Spanish.